2002
DOI: 10.1080/1061186021000038364
|View full text |Cite
|
Sign up to set email alerts
|

Drug Targeting by Solid Lipid Nanoparticles for Dermal Use

Abstract: Long term topical glucocorticoid treatment can induce skin atrophy by the inhibition of fibroblasts. We, therefore, looked for the newly developed drug carriers that may contribute to a reduction of this risk by an epidermal targeting. Prednicarbate (PC, 0.25%) was incorporated into solid lipid nanoparticles of various compositions. Conventional PC cream of 0.25% and ointment served for reference. Local tolerability as well as drug penetration and metabolism were studied in excised human skin and reconstructed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…SLNs used for topical application for various drugsuch as anticancer [16], vitamin-A [17], isotretinoin, flurbiprofen [18].Using glyceryl behenate, vitamineA-loaded nanoparticles can be prepared. Thismethod is useful for the improvement ofpenetration with sustained release.…”
Section: Slns For Topical Usementioning
confidence: 99%
“…SLNs used for topical application for various drugsuch as anticancer [16], vitamin-A [17], isotretinoin, flurbiprofen [18].Using glyceryl behenate, vitamineA-loaded nanoparticles can be prepared. Thismethod is useful for the improvement ofpenetration with sustained release.…”
Section: Slns For Topical Usementioning
confidence: 99%
“…The report show an improved extent of prednicarbate uptake by human skin in vitro, if applied as SLN dispersion or cream containing prednicarbate-loaded SLN. The authors found that a prednicarbate targeting to the epidermis [189]. This is particular relevant because prednicarbate in the dermis is responsible for the induction of irreversible skin atrophy while the inflammatory process is most pronounced within the epidermis [186].…”
Section: Applications Of Nanocarrier Systems In Topical/transdermal Dmentioning
confidence: 99%
“…Besides, the drug targeting to the skin or even to its substructures could be realized by micro-and nanoparticulate systems [40,41]. These drug carrier systems could target glucocorticoids to the viable epidermis, where the inflammatory reactions take place [9]. In particular, liposomal preparations showed strong affinity for the SC [42].…”
Section: Formulations Of Tcmentioning
confidence: 99%
“…In particular, liposomal preparations showed a strong affinity for the SC. Patents filed on topical nanoparticulate formulations also claimed the importance of colloidal drug carrier systems for this type of applications [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%